Aktuelle temaer i regnskap og revisjon - Stenheim, Tonny; Baksaas, Kjell Magne; Kulset, Ellen M. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"Topics in Accounting and Auditing is a scientific anthology with articles shedding light on relevant issues in financial accounting and auditing. The book also contains articles in the adjacent subject areas of non-financial reporting and management accounting. Topics covered in the book range from accounting regulation, accounting theory and accounting practices via topics in audit methodology to topics in non-financial reporting. The book's contributors hold academic positions at the University of South-Eastern Norway, the Norwegian School of Economics, the Norwegian University of Science and Technology, the Nord University and the Inland Norway University of Applied Sciences. They are all experts in their fields. The book's target group is master's students in accounting and auditing, researchers and lecturers in accounting and auditing, accounting and auditing regulators, and practitioners who prepare, audit or use accounting information."